Improved frozen section examination of the retroareolar margin for prediction of nipple involvement in breast cancer. Issue 8 (August 2015) - Morales Piato, J.R.; Aguiar, F.N.; Mota, B.S.; Ricci, M.D.; Dória, M.T.; Alves-Jales, R.D.; Messias, A.P.; Filassi, J.R.; Baracat, E.C.
Abstract Introduction In this prospective ex vivo study, we propose a new technique for the intraoperative examination of retroareolar tissue and describe both surgical excision and pathological methods. We performed a nipple-sparing mastectomy simulation in patients selected to total mastectomy, in order to evaluate the accuracy of these new technique. Materials and methods A total of 158 total mastectomy specimens from patients affected by ductal carcinoma in situ (n = 15) or invasive ductal carcinoma (stages I, II, or IIIA) (n = 143) were examined. To obtain the entire sample area, the terminal retroareolar milk duct bunch was isolated. Fragments approximately 1.5 cm in length were excised and sectioned in parallel at the base of the nipple using a cold bistoury. Three transverse histological sections (4 μm each) at 200 μm intervals that included the entire isolated fragments were subjected to frozen section examination. The sections were stained with hematoxylin-eosin and were evaluated. The remainder of each fragment was embedded in paraffin and 4 μm sections were subsequently stained with hematoxylin-eosin and examined. Results There were two false-negative (1.3%) and five false-positive (3.1%) findings among the frozen and paraffin sections analyzed. A statistical analysis of the frozen section examinations showed a sensitivity of 92.0%, a specificity of 96.2%, a positive predictive value of 82.1%, a negative predictive value of 98.4%, and an accuracy of 95.4%. Conclusion The frozen section examination technique described here detected nipple involvement in breast cancer with greater accuracy than the frozen section usually performed by most surgeons.